Data Integrity and Performance Comparison of New Type- Based Proxy Re-encryption (TB-PRE) and Provable Data Possession (PDP) in Mobile Cloud Computing - Chamoli, Ankit; Goyal, Anshika (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing gives shared pool of assets (computers resources like networks, server and storage) on the demand of the user in ubiquitous and simple way that can be provisioned to the user with a very little management effort. The basic concept of cloud computing can be understood by the following definition according to NIST. It can be concluded from the above discussions that the demands required by the user are fulfilled by the cloud computing. These demands include both hardware and software resources which are present on the internet. A shared pool of resources is provided by the cloud computing provider which can be accessed by the users as per their demands. The users subscribe as per their requirements and access the resources until it wants to. Virtualization is the technique which helps in providing such services and also in reducing the cost of implementation and also adding hardware parts which will help in meeting the requirements of the user. The PDPT and NTBPRET are the techniques which ensure the data integrity.